2017
DOI: 10.1111/1462-2920.13662
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of copper resistance in the kiwifruit pathogen Pseudomonas syringae pv. actinidiae through acquisition of integrative conjugative elements and plasmids

Abstract: Horizontal gene transfer can precipitate rapid evolutionary change. In 2010 the global pandemic of kiwifruit canker disease caused by Pseudomonas syringae pv. actinidiae (Psa) reached New Zealand. At the time of introduction, the single clone responsible for the outbreak was sensitive to copper, however, analysis of a sample of isolates taken in 2015 and 2016 showed that a quarter were copper resistant. Genome sequences of seven strains showed that copper resistance - comprising czc/cusABC and copABCD systems … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 74 publications
(99 reference statements)
1
65
1
Order By: Relevance
“…The encoded amino acids sequences whose function could be recognized according to RAST annotation were exclusively phage associated proteins (Table S4 ). Hence, we could find no evidence of gene gain in our sample of 12 European genomes, reveling a picture divergent from that described by Colombi et al ( 2017 ) who showed the acquisition by strains isolated in New Zealand of exogenous integrative conjugative elements carrying copper resistance genes during clonal expansion.…”
Section: Resultscontrasting
confidence: 82%
“…The encoded amino acids sequences whose function could be recognized according to RAST annotation were exclusively phage associated proteins (Table S4 ). Hence, we could find no evidence of gene gain in our sample of 12 European genomes, reveling a picture divergent from that described by Colombi et al ( 2017 ) who showed the acquisition by strains isolated in New Zealand of exogenous integrative conjugative elements carrying copper resistance genes during clonal expansion.…”
Section: Resultscontrasting
confidence: 82%
“…These authors suggested that these distinctive clades are the result of various gene-shifting processes derived from different source populations, hinting at the likely probability of new virulence emergence in Psa populations. In fact, evidence suggests selection driving horizontal gene transfer in a Psa -V strain to gain copper resistance from a local Psa -LV strain ( Colombi et al, 2017 ). Considering the active transfer and conversion events of virulence effector genes in Psa source populations, research efforts on the effector gene pools in geographically co-existing strains such as Psa- LV and Psa- V would be useful.…”
Section: Introductionmentioning
confidence: 99%
“…Few of those products reduced disease incidence significantly and consistently (Vanneste, 2013). Today, the industry relies mostly on copper-based products to limit the impact of the disease (Colombi et al, 2017), most of them authorized for winter treatment and effective against other bacterial pathogens on kiwifruit, such as P. syringae pv. syringae and Pseudomonas viridiflava (Fratarcangeli et al, 2010).…”
Section: Introductionmentioning
confidence: 99%